2021
DOI: 10.1002/ijch.202100035
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Proton Coupled Electron Transfer in the Field of Artificial Photosynthesis

Abstract: Artificial photosynthesis with respect to water splitting is usually divided into water oxidation catalysis (WOC) and the hydrogen evolution reaction (HER). Though in the combined redox dissociation of water into oxygen and hydrogen no protons and electrons occur, both half reactions show photoinduced proton coupled electron transfer (PCET). Regarding a classical approach, photosensitizers (PS) deliver electrons and protons that are accepted by water reduction catalysts (WRC) containing suitable basic atoms li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 70 publications
0
6
1
Order By: Relevance
“…By contrast, for EPT or PET the electron transfer is assumed to be the rate determining step, where none or a small KIE is measurable. 89 to nickel catalysts is in contrast to previous results, which likely arise from different irradiation conditions like the duration (5.5 h vs. 60/120 min), the light source (150 W Hg lamp vs. LED) and the WRC/PS ratio (10 vs. 5).…”
Section: The High Availability Of Excited Electrons May Correspond Withcontrasting
confidence: 96%
“…By contrast, for EPT or PET the electron transfer is assumed to be the rate determining step, where none or a small KIE is measurable. 89 to nickel catalysts is in contrast to previous results, which likely arise from different irradiation conditions like the duration (5.5 h vs. 60/120 min), the light source (150 W Hg lamp vs. LED) and the WRC/PS ratio (10 vs. 5).…”
Section: The High Availability Of Excited Electrons May Correspond Withcontrasting
confidence: 96%
“…Proton–electron transfer (PET) is a fundamental reaction in electrochemistry, 1–3 biochemistry, 4,5 material science, 6,7 and in some other fields. 8,9 To give one example, we can consider the charging and discharging processes in aqueous redox flow batteries, 10–14 in which the two elementary steps, i .…”
Section: Introductionmentioning
confidence: 99%
“…23 Inserted proton relays in the form of an amine function are intended to facilitate proton binding, the proton transfer and hydride binding to the catalytic metal centre. 9,[25][26][27] Please do not adjust margins Please do not adjust margins It has also been reported that pendant amines support rapid hydride formation and proton-hydride coupling in the immediate vicinity of the metal centre, leading to increased hydrogen formation rates. Beyond that, it is assumed that the basicity of the neighbouring amines in interaction with the hydride acceptor capability of the metal centre favours thermodynamically favourable processes, which leads to higher and faster hydrogen evolution.…”
Section: A Introductionmentioning
confidence: 99%
“…23 Inserted proton relays in the form of an amine function are intended to facilitate proton binding, proton transfer and hydride binding to the catalytic metal centre. 9,25–27…”
Section: Introductionmentioning
confidence: 99%